(untitled) (American Journal of Economics and Business Innovation, 2023)
Entrepreneurial activities, especially social entrepreneurship, are acclaimed to foster resilience. A social entrepreneurship One Acre fund program was introduced in western Kenya to help improve maize production on one acre pieces of land occupied by many households. However, One Acre Fund households in Kakamega county still suffer deficiency in income growth, job creation, meeting health and education obligations of their families, food security, and payment of other family bills despite engaging all the social entrepreneurship strategies, Literature identifies five social entrepreneurship strategies that help in fostering resilience of household livelihoods. These are: system reform, physical capital development, individual empowerment, collective action, and earned income strategies. All five strategies are seldom studied together in relation to resilience of household livelihoods but their impacts are unknown. Frequencies and percentages were used to analyze demographic factors while inferential statistics-moderated multiple regression was used to analyze how social entrepreneurship strategies and social innovation are related to resilience of household livelihoods. The findings revealed that social entrepreneurship strategies statistically significantly contributed to resilience of One-Acre Fund household livelihoods with (β=.652, t(311)=15.103, p=.000) that accounted for 42.3% change in resilience of One-Acre Fund household livelihoods(R2=0.423,F(1,309=228.101, p=.000), The study recommends that as a coping mechanism to food insecurity, farmers should adopt one acre fund model. This study advises the policy makers to consider the production of maize by use of one-acre fund skills as a social entrepreneurship to minimize the inefficiency levels and increase production by minimizing the cost of inputs and cost of capital The study highlights the applicability of social entrepreneurship in a new context and further facilitates the creation of knowledge and growth of literature in social entrepreneurship.